(untitled) (Fiep Bulletin - online, 2015)
The habitual doing of sports and physical activities, as a pleasure activity, as seen on the South beaches of Rio de Janeiro city, has effect on the personal development of the practitioners as well as due to the cultural identity of the city. Among these sports practiced in “free air” , especially on the sand of the beaches, one may find the “futevôlei”, that is, a mixture of soccer and volleyball played in a volley square on the beach. This sport was created in the early 60´s, between 1964 and 1965 by a young group of people commanded by an ex-soccer player of a club called “Botafogo Futebol de Regatas”. His name was Otávio. At that time, the police prohibited the practice of soccer and the transference of a ball from one player to another until four p.m. on the beach. However, Otávio and his friends decided to create a hybrid soccer sport and play volleyball on the beach. Its identity was developed based on the differences from these two sports. The main goal of this study is to understand the “futevôlei”-soccer-volley- as a display of pleasure in the pertaining to sports culture on the beach. The specific aims are: (a) to describe the phenomenon of the “futevôlei”(soccer-volley) as a cultural activity on Copacabana Beach; (b) to investigate the real sense of this adventure exposed in the speech of the practitioners who play “futevôlei” in a playful space like the sand of Copacabana beach; (e) to make clear symbolic and mythic elements presented in the futevôlei culture, which make players move on their action on the sand of Copacabana. This study has a qualitative nature, that comes to grips with an ethnographic interpretation, based on the six first pioneers of this sport. We chose as a methodological strategy semi-structured interview approaches and systematic observation of the game view. The conclusion is that the “futevôlei” happens because of the myths and beliefs influences that dominate a culture that has been involved its origin: the male superiority, the astuteness of recreating the daily life by means of the playful carioca´s spirit, based on an ethic that has its life survival as means of excitement and adventure on the pertaining to sports pleasure.